THE EFFECT OF FOREIGN INVESTMENT AND INTERNATIONAL PRICES ON EXPORT VOLUME IN THE GARMENT SECTOR (CONVECTION) OF INDONESIAN TEXTILES WITH EXPORT VAT RESTITUTION POLICY AS A DUMMY VARIABLE FOR 2005-2019 - Yunita Tri Andina; Saparuddin Mukhtar; Dicky Irianto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Export is one of the international trades that can increase the country's economy and foreign exchange. This study aims to determine the effect of foreign investment and international prices on the export volume of apparel (convection) from Indonesian textiles with the Export VAT Restitution Policy as a Dummy Variable for 2005-2019. This research is quantitative research. The method used in this study is a simple regression method with the OLS model. The results of the study highlight that the foreign investment variable and international prices had a significant effect on the export volume of Indonesian apparel, but the export VAT restitution policy had no effect on the export volume of Indonesian apparel because other policies were needed to support these policies in order to increase exports.